Improved computational fluid dynamics modelling of coal spontaneous combustion control and gas management. (15th September 2022) - Qiao, Ming; Ren, Ting; Roberts, Jon; Liu, Hongwei; Yang, Xiaohan; Tan, Lihai; Wu, Jianming
Highlights: Qualitative and quantitative analysis of simulation results. The ratio of oxidation zone area and goaf area was introduced. Impact of mining parameters on spontaneous combustion management was studied. Goaf inertisation strategies were optimized for spontaneous combustion control. The usage of curtains for methane mitigation at the tailgate end was studied. Abstract: Computational fluid dynamics (CFD) is an effective methodology that has been widely used for decades to solve engineering problems involving spontaneous combustion and abnormal gas emissions. However, most of the previous CFD modelling focused on qualitative rather than quantitative analysis, and the factors influencing spontaneous combustion control and gas management are numerically under-researched. The onset of spontaneous heating in the goaf area is dictated by many operational and environmental parameters, including mining method, ventilation and geology. Based on field data from a real mine site, extensive CFD modelling was conducted and analyzed qualitatively and quantitatively to investigate the impact of ventilation design and operational measures on the management and control of spontaneous combustion and gas exceedance. Real-time gas monitoring data was utilized for model validation, and a good agreement between simulation results and monitoring data was reached. The tightness of goaf seals described by permeability was quantitatively investigated, revealing that the permeability should be smaller than 10 −9 m 2 to prevent air leakage effectively. Goaf inertisation parameter optimization is crucial to minimize the risk of spontaneous combustion. The systematic study revealed that the oxidation zone area (OZA) was the largest for nitrogen injection (29706 m 2 ), followed by boiler gas (28396 m 2 ), while it was the smallest for carbon dioxide (11902 m 2 ), which produced the best goaf inertisation performance. Injection flow rate is another significant factor influencing the effectiveness of heating prevention. The simulation results indicated that a critical injection rate of 1750 m 3 /h was determined, and the ratio of the OZA to the goaf area (GA) fluctuated around 7% once the injection rate was beyond this critical value. The installation location of curtains and brattices both on the longwall face and tailgate end was also simulated and optimized. Noticeable methane reduction at the tailgate end was observed with optimal configurations of brattices and curtains. Results from the modelling will shed light on improving current practices to effectively contain goaf heating in the longwall goaf areas and mitigate methane exceedance on the longwall face.